"A Nation Depends on Its Children": School Buildings and Citizenship in England and Wales, 1900–1939. (15th April 2015) - Hulme, Tom
Abstract: Calls for a renewed sense of "good citizenship" in the early twentieth century were loud and persistent. Especially important in the citizenship quest was the creation of healthy and efficient children, cured of urban maladies and loyal to a wide notion of community. Such attributes were seen as vital in an economically and militarily competitive world. Historians have already examined the sorts of political and bodily education that arose from these concerns. This article instead looks at how the focus on the body and citizenship was realized in the actual processes of school building. From the medical discourses that underpinned the design of heating, lighting, and ventilation systems, to the emerging focus on the sensory environment of the classroom, the materiality of the school was essential to creating the "good citizen"—physically fit, economically productive, and loyal to the nation.